Ti-iminocarboxylate catalyzed polymerization of ethylene to highly crystalline, disentangled, ultrahigh molecular weight polyethylene - Bodkhe, Dnyaneshwar V.; Chikkali, Samir H. (European Polymer Journal, 2023)
Disentangled ultrahigh molecular weight polyethylene (d-UHMWPE) is a niche, highly sought-after, and an emerging class of polyethylene. However, the synthesis of d-UHMWPE is uncommon and is equally challenging. Here, we report a Ti-iminocarboxylate complex that produces d-UHMWPE under ambient polymerization conditions. Treatment of tetrakis(dimethylamido-titanium) [Ti(NMe2)4] with 2-((4-methoxybenylidene)amino)benzoic acid produced a novel titanium complex Cat.1 [bis-dimethylamido-Ti-(bis-iminocarboxylate)]. The identity of Cat.1 was unambiguously ascertained using a combination of 1-2D NMR spectroscopy and mass analysis. Cat.1 was activated using various cocatalysts, and MMAO (modified methylaluminoxane) outperformed the others. Screening of polymerization parameters suggested an Al/Ti ratio of 1000, 4 bar ethylene pressure, 35 degrees C temperature, and a polymerization time of 30 min as the optimal condition. Under the optimized polymerization conditions, Cat.1 polymerizes ethylene to ultrahigh molecular weight polyethylene with a weight average molecular weight (Mw) of 2.5 x 106 g/mol. The thermal behavior of the thus prepared material disclosed a highly crystalline [crystallinity chi (DSC) 96 %], strictly linear polyethylene. Detailed thermal analysis of the nascent polyethylene using a specifically designed DSC method revealed the existence of a high melting peak at 139-140 degrees C, which is a hallmark of disen-tangled UHMWPE. Thus, a homogeneous, single-site ethylene polymerization catalyst has been developed, which upon activation with MMAO produced highly crystalline d-UHMWPE.